Influência do uso de um aplicativo m-Health nas condições de saúde de pacientes com hipertensão - Debon, Raquel (2019)
Hypertension is considered one of the main modifiable risk factors for diseases of the circulatory system and one of the most important public health problems. The World Health Organization estimates that about 600 million people have Systemic Arterial Hypertension and annually 7.1 million go to death as a result of this disease, generating costly health systems. Adopting a healthy l ifestyle is an important ally for maintaining blood pressure (BP) at the recommended levels. However, healthy habits need to be adopted from childhood, that is, throughout the aging process, so that it does not cause future problems. Controlling BP is still a challenge, because with day-to-day activities and lack of time, many people do not bother to maintain normal pressure levels. The use of m-Health applications can help improve health conditions and blood pressure levels. To this end, the e-Lifestyle application was developed to help monitor the health conditions of hypertensive patients with a view to encouraging a healthy lifestyle. In this context, the objective of this dissertation was to evaluate the effects of the use of the e -Lifestyle system in improving the health conditions of hypertensive patients treated in the public health network. This is a non-randomized, controlled, non-blind clinical trial comparing the use of an m-Health application with conventional HA treatment for a period of three months in patients with hypertension aged 18-80 years , attended at ESF 1º Centenário and Nenê Graeff, located in the municipality of Passo Fundo. The sample was stratified into two groups: Intervention Group (GI), which performed the intervention using the e-Liefestyle app and Control Group (GC), which did not receive any form of intervention, besides the conventional treatment during the research. The instruments used for the evaluation were: Mini Mental State Examination (MEMM), Checklist with the requirements to participate in the research, Sample characterization questionnaire, Food Frequency Questionnaire (QFA), "Appraisal of Self-Care Agency Scale (ASA - A) "Self - care, and blood count tests, Creatinine, Uric acid, Sodium and potassium, Total cholesterol, HDL and triglycerides and Glycemia, Spherical and Diastolic Blood Pressure gauging. At the end of this study, the results presented were positive, the use of the e -Lifestyle application showed improvements in the health conditions of patients with AH. Among the improvements observed in both groups are the reduction in total and non-HDL cholesterol, healthier consumption in relation to salads and soft drinks, and increased self-care according to the ASA-A scale. However, the GI that used the m-Health application performed better. The use of technologies associated with health is a positive advance that helps to treat patients with hypertension, providing greater adherence to treatment, healthier habits and better health conditions complementing the actions already existing with the ESF. The results of this dissertation are presented in the form of a scientific article.